Vision, narrative, and wisdom in the Aramaic texts from Qumran : essays from the Copenhagen Symposium, 14-15 August, 2017 - Bundvad, Mette, 1982-; Siegismund, Kasper; Bach, Melissa Sayyad; Holst, Søren; Høgenhaven, Jesper (Studies on the texts of the desert of Judah, 2020)
"The Aramaic Dead Sea Scrolls from Qumran have attracted increasing interest in recent years. These texts predate the "sectarian" Dead Sea scrolls, and they are contemporary with the youngest parts of the Hebrew Bible. They offer a unique glimpse into the situation before the biblical canons were closed. Their highly creative Jewish authors reshaped and rewrote biblical traditions to cope with the concerns of their own time. The essays in this volume examine this fascinating ancient literature from a variety of different perspectives. The book grew out of an international symposium held at the University of Copenhagen in August 2017"--